IMPLEMENTASI HADIS TA’AWUN DALAM MEKANISME TABARRU’: STUDI KASUS PRODUK PRULINK SYARIAH GENERASI BARU - Rachma Febriyanti; Muhammad Yahya; Sitti Asiqah Usman Ali (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
Hadith holds an important position as the second source of Islamic teachings, serving not onlyas a basis for legal rulings but also shaping social and economic values. This study aims toanalyze how the principle of ta’awun (mutual assistance) found in authentic hadiths isimplemented through the tabarru’ mechanism in Islamic life insurance products in Indonesia.This research employs a qualitative descriptive approach using a library research method, byvalidating the sanad and matan of the hadith and analyzing the content of Islamic lifeinsurance policy documents. The result shows that the tabarru’ mechanism in Islamic lifeinsurance genuinely applies the value of solidarity through contribution-based donations,shared risk claim schemes, surplus underwriting arrangements, and an interest-free qardh(benevolent loan) mechanism. These findings demonstrate that the principle of ta’awun,derived from authentic hadith and supported by Quranic verses, can be practically andsystematically actualized through the tabarru’ mechanism as a risk protection instrumentbased on Islamic principles. This study is expected to enrich the literatur on applied hadithstudies and provide input for the development of Islamic finansial practices that remainaligned with authentic sources.